A framework for characterizing knowledge management systems. - Pinto, Mário Paulo (2005)
This paper presents a framework for characterizing knowledge management systems (KMS). The framework has a descriptive nature and aims to be useful both to characterize and to drive KMS implementations, facilitating the identification and selection of appropriate tools according organization needs. A review of KMS categories was made to identify their underlying assumptions and purposes, and a systematization of intellectual capital (IC) measurement models was developed with the purpose of identifying the main components normally used to measure IC and to analyse if those measures are addressed by KMS.